2020
DOI: 10.3389/fimmu.2020.00281
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Regulatory Mechanism of Hippo Signaling Components in the Neuronal System

Abstract: The Hippo signaling pathway, an evolutionarily conserved protein kinase cascade, plays a critical role in controlling organ size, cancer development, and tissue regeneration. Recently, mounting evidence has suggested that Hippo signaling also has an important role in regulating immunity, including innate and adaptive immune activation. In the neuronal system, Our laboratory results, together with those from other studies, demonstrate that the Hippo signaling pathway is involved in neuroinflammation, neuronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…Recently, mounting evidence has shown the important role of Hippo/YAP signaling in CNS homeostasis. Dysfunction of Hippo/YAP signaling contributes to negative proapoptotic and proinflammatory effects in CNS diseases [ 15 ]. During cerebral ischemic injury, YAP deletion aggravates BBB and astrocyte damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mounting evidence has shown the important role of Hippo/YAP signaling in CNS homeostasis. Dysfunction of Hippo/YAP signaling contributes to negative proapoptotic and proinflammatory effects in CNS diseases [ 15 ]. During cerebral ischemic injury, YAP deletion aggravates BBB and astrocyte damage.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other core proteins of the Hippo signaling pathway (MSTs, LATS, and TAZ), YAP has been suggested to be strictly located in astrocytes and neural stem cells. Specifically, members of the TEAD family, including TEAD1, TEAD2, and TEAD3, are the core transcription factors of YAP in the nucleus and are expressed in astrocytes [ 15 ]. YAP, the transcriptional coactivator of Hippo signaling, has largely been studied for its role in the immune response and as a potential transcriptional regulation of the tumor checkpoint receptor PD-1 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies implicate its role in neural functions, such as neuroinflammation and neuronal cell death. [37] In hypothalamus, Rap1 signaling pathway was also captured, which is involved in neuronal connectivity, [38] hypothalamic inflammation, and leptin sensitivity. [39] Agreeing with the transcriptome-level findings, the DNA methylation loci affected by DHA under the two dietary conditions were also drastically different.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that abnormal Hippo signaling contributes to the development of tumors [61].Recently, mounting evidence has shown the important role of Hippo/YAP signaling in CNS homeostasis. Dysfunction of Hippo/YAP signaling contributes to negative proapoptotic and proin ammatory effects in CNS diseases [16]. During cerebral ischemic injury,YAP deletion aggravates BBB and astrocyte damage.MST1,another important regulator of YAP in the Hippo pathways, is overactivated in a model of ICH, and knocking down MST1 mitigates in ammatory reactions and neuronal cell death [62].…”
Section: Discussionmentioning
confidence: 99%